Effect of Sunset Policy, Tax Amnesty, Tax Sanctions, and Whistle-Blowing System Against Tax Obligation (An Empirical Study on A Private Vocational Yogyakarta) - Muda, Mudasetia; Ristiana, Ita; Wening, Nur (Universitas Teknologi Yogyakarta, 2020)
This research was conducted to examine the influence of sunset police, tax amnesty, tax sanctions, and the tax blast system on tax complaints. Population checks are all taxpayers at regional offices in the Special Region of Yogyakarta. The sampling method in this study is simple random sampling. The sample is 100 taxpayers with a total of 120. The number of observational data analysis methods used is multiple regression analysis. The results showed that there was no influence on the sunset policy of tax complaints with a significant 0.479 > 0.05. There is no effect of tax amnesty on tax complaints with a significant 0.357 > 0.05. Its influence on tax sanctions tax complaints with a significance of 0.023 < 0.05. Its effect on whistle-blowing tax complaints with a significance of 0.080 < 0.10. The F test simultaneously affected sunset, tax amnesty, tax sanctions, and Whistle-blowing system on tax complaints with a significant 0,000 < 0.05. The coefficient determination test shows the value of 0.158 or 15.8% the dependent variable can be explained from the independent variable and 84.2% is influenced by other variables outside the model. Keywords: Sunset Policy, Tax Amnesty, Tax Sanction, Whistle Blowing System, and Tax Compliance.